Exploring the impacts of contextualised outdoor science education on learning: the case of primary school students learning about ecosystem relationships - Ayotte-Beaudet, Jean-Philippe; Chastenay, Pierre; Beaudry, Marie-Claude; L’Heureux, Kassandra; Giamellaro, Michael; Smith, Jonathan; Desjarlais, Estelle; Paquette, Alain (Journal of Biological Education, 2021)
The present study explored the impacts of a contextualised outdoor science curriculum on what and how elementary students learn when immersed in the local contexts in which natural phenomena occur. We conducted 63 individual interviews with fifth- and sixth-graders (between 10 and 12 years old) living in the inner city of Montréal, Québec province, Canada. These allowed us to identify (1) three categories of impacts on what students learned: evolution of conceptual understanding about living organisms, development of scientific investigation abilities, and evolution of connection to nature, and (2) two categories of impacts on how students learned: a context that encourages deeper learning and a context that promotes engagement. Our results show that impacts on students went beyond learning about living organisms. A strength of our findings is that although the method of data collection did not aim a priori to corroborate the work of other research in the field of outdoor education, it in fact corroborated several results from other research, which is an important step for the development of this field. We also found that some students developed a connection to nature without addressing environmental problems during outdoor activities.
Keywords: Science education; contextualisation; outdoor science; primary school students